A Management Model of Scout Activities for Enhancing Life Skills of Students in Opportunity Expansion Schools, Nong Bua Lamphu Province - Sawaengkamrai, Thongchai; Phakamach, Phongsak; Pangthai, Sasirada (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aimed to: 1) examine the current state, desirable state, and priority needs of Scout activity management in opportunity expansion schools; 2) develop a management model for Scout activities to enhance students’ life skills; and 3) evaluate the propriety, feasibility, and effectiveness of the developed model. This study employed a research and development (R&D) design, conducted in three phases: situational and problem analysis, design and development, and evaluation. The sample consisted of 300 participants, including school administrators, teachers, and students, selected through multi-stage random sampling. The research instruments comprised questionnaires, in-depth interviews, a three-dimensional model evaluation form, and a life skills assessment scale. All instruments were validated for content validity, reliability, and construct validity. Quantitative data were analyzed using mean and standard deviation, while qualitative data were analyzed through content analysis. The findings indicated that while most schools followed prescribed Scout activity guidelines, they faced significant constraints regarding personnel and resources. A substantial number of responsible teachers lacked specialized Scout training. Furthermore, schools expressed a high demand for a clear management model and assessment tools that accurately reflect life skills development. The developed model consists of eight core components: 1) Planning, 2) Organizing, 3) Leading, 4) Controlling, 5) Monitoring and Evaluation, 6) Scouting Method Implementation, 7) Scout Personnel Development, and 8) Budget and Resource Allocation. Expert evaluation and field testing demonstrated that the propriety, feasibility, and effectiveness of the model were at the highest level. Additionally, students’ life skill scores increased significantly at a statistically significant level.